1852 Haw. Sess. Laws 19, § 1 - (:unkn) unknown (My University, 1852)
Prohibited the carry of any Bowie-knife, sword-cane, air gun, slung-shot, or other deadly weapon. Violators fined no less than ten but no more than thirty dollars.
Keywords: CARRY